2018
DOI: 10.1007/s00330-017-5165-5
|View full text |Cite
|
Sign up to set email alerts
|

To share or not to share? Expected pros and cons of data sharing in radiological research

Abstract: The aims of this paper are to illustrate the trend towards data sharing, i.e. the regulated availability of the original patientlevel data obtained during a study, and to discuss the expected advantages (pros) and disadvantages (cons) of data sharing in radiological research. Expected pros include the potential for verification of original results with alternative or supplementary analyses (including estimation of reproducibility), advancement of knowledge by providing new results by testing new hypotheses (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The attention to inter- and intra-reader variability [ 19 ] and the work committed to improve the repeatability and reproducibility of medical imaging over the past decades proves the need for reproducible radiological results. In a broader perspective, the trend toward data sharing also works in this case [ 20 ]. The key point is that AI has the potential to replace many of the routine detection, characterisation and quantification tasks currently performed by radiologists using cognitive ability, as well as to accomplish the integration of data mining of electronic medical records in the process [ 1 , 7 , 21 ].…”
Section: Ai In Radiology: Threat or Opportunity?mentioning
confidence: 99%
“…The attention to inter- and intra-reader variability [ 19 ] and the work committed to improve the repeatability and reproducibility of medical imaging over the past decades proves the need for reproducible radiological results. In a broader perspective, the trend toward data sharing also works in this case [ 20 ]. The key point is that AI has the potential to replace many of the routine detection, characterisation and quantification tasks currently performed by radiologists using cognitive ability, as well as to accomplish the integration of data mining of electronic medical records in the process [ 1 , 7 , 21 ].…”
Section: Ai In Radiology: Threat or Opportunity?mentioning
confidence: 99%
“…Efforts should be instead paid to the researchers' training and to policies that may further improve research quality, such as a priori registration of a trial protocol, the need for a professional statistician for data analysis, and data sharing [6]. Especially, data sharing has the potential for verification by independent authors of the results presented in a given publication [28]. When data are shared, they may be used by other researchers to perform alternative or supplementary analyses.…”
Section: Beyond the P Value: Secondary Evidence And Data Sharingmentioning
confidence: 99%
“…This may be facilitated by requiring the checklist to be viewed before beginning a study, with responses submitted to a research the clinical impact by involving interested members of the scientific community who were not directly involved in the primary trial (48,49). However, a recent study showed that only three of 18 general imaging journals encouraged data sharing and only one journal requested it (48). Structured reporting in radiology clinical practice will certainly improve the potential for data sharing beyond clinical trials.…”
Section: Enhancing Global Collaborationmentioning
confidence: 99%